The philosophical aspects of education internationalization on Belarusian territories in XVI–XVIІІ centuries - Smaliakou, Dzmitry A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article observes the scholastic basement of genesis and development of education on Belarusian territories XVI–XVIІІ centuries in accordance with processes of internationalization in area of intellectual and cultural exchange with Western Europe. There is also investigated the parallel process of experimental methodology implementation into local university education which was completed in framework of Education Commission activities and Enlightenment ideas realization in area of Polish-Lithuanian Commonwealth education system reform.
Keywords: internationalization of education; scholasticism; philosophia recentiorum; Enlightenment; inter-confessional polemics; Jesuit Academy of Wilnia